Forms of the spiritual culture living of Koho people in Lam Dong - Nguyễn Thị Như Thúy (Journal of Technical Education Science, 2014)
Spiritual culture life is one of the important indicators to recognize the development, advances of human in the process of absorbing, continued development of new cultural values as well as preserve traditional cultural values of community, society. Through which, we can see the harmonious development, complement each other or have the differences, lame between traditional cultural values with new cultural values by the media bring. With that meaning, we find out “Forms of the spiritual culture living of Koho people in Lam Dong”.